Perancangan Sistem Informasi Sewa Kontrakan Pada Perumahan Gasela Pinang Awan Berbasis Android - Anggi Yulia Fani (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2022)
At present the increasing competition for business, then in line with the development of existing information. The dynamic economic conditions in Indonesia cause many companies engaged in property must be careful in determining the steps in marketing products that are being developed, and also must be creative in marketing, property companies must be able to maintain to meet the demands of rental housing to be rented . The purpose of the research is To produce a system that is used in the community and makes it easier to search for a rented house. The data collection method is used by the author to obtain data as a study material in writing the final project with the aim of making an Application for Boarding Information or a rental house in Labuhanbatu. In this case the authors use data collection methods in the form of primary data sources (observation, interviews) and secondary data sources.